INSTITUSIONALISASI AKAD MUAMALAH (Studi Transformasi tentang Proses dan Alur Migrasi Akad Personal ke Akad Institusi dalam Perbankan Syariah) - Ali Amin Isfandiar (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2009)
Islamic contract mechanism, as it's called al-'aqd al-muamalah) was done as personal contract. The emerging of islamic bank makes it transfrormed being an institution contract, that changes a simple contract being a rigid one, because a position of the islamic bank. This process is called by